Single nucleotide polymorphism array (SNP-array) analysis for fetuses with abnormal nasal bone - Xie, Xiaorui; Su, Linjuan; Li, Ying; Shen, Qingmei; Wang, Meiying; Wu, Xiaoqing (Archives of gynecology and obstetrics, 2024)
Purpose This study aims to evaluate the prevalence of submicroscopic chromosomal abnormalities found on single nucleotide polymorphism array (SNP array) in pregnancies with either an absent or hypoplastic nasal bone. Methods This retrospective study included 333 fetuses with either nasal bone hypoplasia or absence identified on prenatal ultrasound. SNP array analysis and conventional karyotyping were performed in all the subjects. The prevalence of chromosomal abnormalities was adjusted for maternal age and other ultrasound findings. Fetuses with either an isolated nasal bone absence or hypoplasia, those that had additional soft ultrasound markers, and those where structural defects were found on ultrasound were divided into three groups: A, B, and C, respectively. Results Among the total cohort of 333 fetuses, 76 (22.8%) had chromosomal abnormalities, including 47 cases of trisomy 21, 4 cases of trisomy 18, 5 cases of sex chromosome aneuploidy, and 20 cases of copy number variations of which 12 were pathogenic or likely pathogenic. The prevalence of chromosomal abnormalities in group A (n = 164), B (n = 79), and C (n = 90) was 8.5%, 29.1% and 43.3%, respectively. The incremental yields by SNP-array compared with karyotyping in group A, B, and C were 3.0%, 2.5% and 10.7%, respectively (p > 0.05). Compared to karyotype analysis, SNP array detected an additional 2 (1.2%), 1 (1.3%), and 5 (5.6%) pathogenic or likely pathogenic CNVs in groups A, B, and C, respectively. In the 333 fetuses, the prevalence of chromosomal abnormalities in women with advanced maternal age (AMA) was significantly higher than that in non-AMA women, (47.8% vs. 16.5%, p < 0.05). Conclusion In addition to Down’s syndrome, many other chromosomal abnormalities are present in fetuses with abnormal nasal bone. SNP array can improve the prevalence of chromosomal abnormalities associated with nasal bone abnormalities, especially in pregnancies with non-isolated nasal bone abnormalities and advanced maternal age.